Avatar realism and social interaction quality in virtual reality - Roth, Daniel; Lugrin, Jean-Luc; Galakhov, Dmitri; Hofmann, Arvid; Bente, Gary; Latoschik, Marc Erich; Fuhrmann, Arnulph (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2016)
In this paper, we describe an experimental method to investigate the effects of reduced social information and behavioral channels in immersive virtual environments with full-body avatar embodiment. We compared physical-based and verbal-based social interactions in real world (RW) and virtual reality (VR). Participants were represented by abstract avatars that did not display gaze, facial expressions or social cues from appearance. Our results show significant differences in terms of presence and physical performance. However, differences in effectiveness in the verbal task were not present. Participants appear to efficiently compensate for missing social and behavioral cues by shifting their attentions to other behavioral channels.